FLUID REGIME AND ORE FORMATION IN THE TUNGSTEN(-YTTRIUM) DEPOSITS OF KYZYLTAU (MONGOLIAN ALTAI): EVIDENCE FOR FLUID VARIABILITY IN TUNGSTEN-TIN ORE SYSTEMS - Graupner T.; Kempe U.; Leeder O.; Spooner E.T.C.; Dombon E.; Pätzold O. (My University, 1999)
The Kyzyltau ore field is located in the northern part of the Mongolian Altai Mountains. W(–Y–Be–Mo) mineralization occurs in veins and stockworks in granites, felsic volcanics, basaltic flows, and conglomerates. The main ore minerals in the veins are wolframite, fluorite, beryl and minor molybdenite. Inclusions in hydrothermal quartz, fluorite and beryl from veins, as well as in magmatic quartz in vein-hosting granites of the Ulaan uul, Buraat uul and Tsunkheg deposits were investigated using microthermometry and laser Raman spectroscopy. Pseudosecondary/primary inclusions in the Kyzyltau ore veins are predominantly liquid-rich aqueous inclusions, containing variable amounts of CO2 as the main gas component, and showing N2/CH4 ratios >1. Secondary inclusions contain no or only trace concentrations of gases, as indicated by clathrate melting. The Th values of pseudosecondary/primary inclusions in veins are between 180 and 433°C. Fluid inclusion data indicate that phase separation processes leading to fluid immiscibility occurred in vuggy quartz II and green fluorite II in the Ulaan uul and Buraat uul ore veins. Phase separation pressures of 100–350 bars were estimated. Fluorite I from the Kyzyltau ore field shows a strong enrichment of HREE and a strong negative Eu anomaly common for rare metal-bearing ore systems. Fluorite II from Buraat uul and Tsunkheg is characterized by a change in the incorporation of rare earth elements (REE) with decreasing HREE contents and a decreasing Eu anomaly. The REE distribution patterns in fluorite II from Ulaan uul remained unchanged compared with fluorite I despite a strong increase in the total REE content. A review of the literature shows that from high-temperature, Fe-rich, K-dominated brines cassiterite ores can precipitate in quartz veins together with Fe–chlorite and Fe–tourmaline (Bolivian type). If phase separation of a gas-rich, low-salinity and Fe-rich fluid occurs, cassiterite–wolframite ores may be deposited (Cornwall/Devon type). The deposits of Kyzyltau are characterized by low-Fe alteration assemblages, a predominance of sodium over potassium, high contents of REE and Y, and a lack of extended tin mineralization despite the tin potential of the ore systems. Fluid inclusion data as well as geochemical and geological indications suggest formation of the tungsten deposits near the tops of Li–F-rich sub-volcanic intrusions. We interpret the pH of the mineralizing fluid to be the main factor controlling wolframite precipitation in the Kyzyltau ore field. Fluid–wall rock interactions, a lowering of the temperature and unmixing processes in the ore fluid generated contributions to neutralization and buffering of the acid CO2-bearing fluid into a pH range where tungstates were precipitated. It can be inferred that formation of tungsten ores without precipitation of extended tin mineralization is possible in deposits characterized by high potential tin and tungsten. According to this inference, tin mineralization may be found in a more favourable setting in the vicinity of the Kyzyltau deposits.